A Bibliometric Review on Sustainable Wellness Tourism - Uula, Mimma Maripatul (Halal Tourism and Pilgrimage, 2025)
Sustainable wellness tourism is one of the tourism segments that is growing rapidly as global awareness of health, well-being, and environmental sustainability increases. This research aims to map the development of global research related to sustainable wellness tourism and identify key themes and future research opportunities. The method used was a descriptive qualitative approach through meta-analysis and bibliometrics-based literature studies on 237 Scopus indexed journal articles. The analysis was performed using the VOSviewer software to visualize the keyword, author, and research cluster maps. The results of the analysis show that sustainable wellness tourism research is grouped into seven main clusters, namely the socio-economic impact of health tourism, the competitiveness of sustainable wellness destinations, wellness tourism during health crises, the integration of ecotourism and sustainability, community-based wellness tourism, cultural and recreational wellness tourism, and the spa tourism economy. These findings confirm that sustainable wellness tourism not only contributes to improving the health and well-being of tourists, but also plays a strategic role in local economic development, environmental conservation, and the achievement of the Sustainable Development Goals (SDGs). This research makes a conceptual contribution by presenting a comprehensive research map as well as recommendations for future research directions that are more integrative and sustainability-based.